Behavioral skills training in scent detection research: Interactions between trainer and animal behavior. Issue 3 (24th April 2019) - Lewon, Matthew; Webb, E. Kate; Brotheridge, Sydney M.; Cox, Christophe; Fast, Cynthia D.
Abstract : Animal trainers working in scent detection programs are responsible for arranging training contingencies as well as for observing and recording animal behavior. We provided behavioral skills training (BST) to animal trainers working with scent detection rats to improve the treatment integrity of scent‐detection research sessions. We evaluated the trainers' behavior at baseline and during the sequential introduction of each component of BST (instructions, modeling, and feedback). We observed incremental improvements in treatment integrity with the introduction of each BST component. Posttraining probes revealed that these improvements were sustained at least 3 weeks post‐BST. As the trainers' behavior was modified during BST, we observed decrements in measures of rat performance. We discuss the nature of these interactions and their implications for the use of BST in scent detection research and in situations in which intervention with one party produces concomitant effects on the behavior of another.